2020
DOI: 10.1021/acs.est.0c01575
|View full text |Cite
|
Sign up to set email alerts
|

Microplastics Aggravate the Bioaccumulation of Two Waterborne Veterinary Antibiotics in an Edible Bivalve Species: Potential Mechanisms and Implications for Human Health

Abstract: Edible bivalves are one of the major types of seafood and may be subject to antibiotic and microplastics (MPs) coexposure under realistic scenarios. However, the effect of MPs on the bioaccumulation of antibiotics in edible bivalves and subsequent health risks for consumers remain poorly understood. Therefore, the bioaccumulation of two frequently detected veterinary antibiotics, oxytetracycline (OTC) and florfenicol (FLO), with or without the copresence of MPs was investigated in the blood clam. Health risks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(45 citation statements)
references
References 57 publications
0
44
0
1
Order By: Relevance
“…The presence of additives and contaminants in microplastics raises concerns about the latter's ability to accentuate the bioaccumulation of some of them which could be intestinal toxics. Indeed, the bioaccumulation of oxytetracycline and florfenicol, two frequently detected veterinary antibiotics, in edible bivalves (clams) was found to be aggravated by coexposure to microplastics (PS particles, 500 nm, 0.26 mg/L) [121]. It has been shown that microplastics carry several known intestinal toxics, such as polybrominated diphenyl ethers [122], cadmium [113,123] and triclosan [124].…”
Section: Microplastics As Carriers Of Intestinal Toxics and Pathogensmentioning
confidence: 99%
“…The presence of additives and contaminants in microplastics raises concerns about the latter's ability to accentuate the bioaccumulation of some of them which could be intestinal toxics. Indeed, the bioaccumulation of oxytetracycline and florfenicol, two frequently detected veterinary antibiotics, in edible bivalves (clams) was found to be aggravated by coexposure to microplastics (PS particles, 500 nm, 0.26 mg/L) [121]. It has been shown that microplastics carry several known intestinal toxics, such as polybrominated diphenyl ethers [122], cadmium [113,123] and triclosan [124].…”
Section: Microplastics As Carriers Of Intestinal Toxics and Pathogensmentioning
confidence: 99%
“…This is especially important, since the longer the retention time of these particles, the more likely it is that they will be transferred to the next trophic level upon consumption [34], as well as the more time chemicals and other compounds have to potentially desorb from the particles [23,32,35]. A multitude of studies have been conducted on the effects of pristine and contaminated plastic particles on the health of marine mussels [36,37], as well as the thus resulting health effect for humans [38] for different compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Asian coasts are, predominantly, the sites were the majority of studies investigating antibiotic occurrence in bivalves have been developed [4,27,33,46,48,53,60,61]. Li et al (2012) investigated the distribution of quinolones, sulfonamides and macrolides using mollusks sampled in nine coastal sites along the Chinese Bohai Sea [4].…”
Section: Occurrence Of Antibiotics In Bivalve Mollusks Harvested In Asiamentioning
confidence: 99%
“…Zhou et al (2020) (2021) analyzed blood clams collected in June 2019 from Yueqing Bay, Zhejiang in China. They developed two studies to investigate the effects of microplastics on the bioaccumulation of oxytetracycline and florfenicol (highly used in the veterinary field) in this bivalve species [60] and to deepen the knowledge about the single and combined effects of veterinary antibiotics and microplastics on the immune responses of bivalves [46]. The content of the two tested antibiotics in collected blood clams before the exposure experiment were found to be below the detection limits of 50 µg/kg and 1 µg/kg for oxytetracycline and florfenicol, respectively [46,60].…”
Section: Occurrence Of Antibiotics In Bivalve Mollusks Harvested In Asiamentioning
confidence: 99%